Factors affecting the housing price in Malaysia / Nor Farahanis Nadia Mohd Yusop - Mohd Yusop, Nor Farahanis Nadia (2018)
This study of “Factors Affecting Housing Price in Malaysia” will concentrated on studying the relationship between Housing Price in Malaysia and the variables selected. This study will examine the significant relationship between dependent and independent variables. The relationship between housing price index (HPI) and the factor which is inflation rate (IF), gross domestic product (GDP) and interest rate (IR). This study involve 30 samples which is annually data from year 1987 until 2016. Besides, there are steps involve in the study which begin with Autoregressive Distributed Lag (ARDL) methods and proceed with descriptive analysis, diagnostic checking, unit root tests, and long run form. In diagnostic checking, some test has been done to check the significant presents of autocorrelation, heteroscedasticity, the normality of data distribution and model specification. Thus, the result in study shows that Housing Price (HPI) has a significant relationship with Inflation rate (IF) and interest rate (IR) while it is not significant with gross domestic product (GDP). As conclusion, the factor affecting housing price in this study is inflation rate, gross domestic product and interest rate